Preliminary experience in minimally invasive videoassisted thyroidectomy (MIVAT) - Del Rio, P.; Sommaruga, L.; Ferreri, et al., G. (Acta Biomedica Atenei Parmensis, 2006)
Background: We report our initial experience in the treatment of thyroid disease with Minimally Invasive Videoassisted Technique (MIVAT) introduced by Miccoli. Methods:We have treated from July to September 2005, 5 patients, with MIVAT. The procedure is carried out through an incision of 15-20 mm 2 cm on sternal notch and the thyroidectomy is performed by dedicated instruments. Results: We have surgically treated 3 follicular hyperplasias, one Hurthle adenoma and one papillary carcinoma. The mean time of thyroidectomy was 98±14 minutes; four cases were discharged after 24 hours and one case after 48 hours for a postoperative hypertension.No hypocalcemia, no nerve palsy. Cosmetic result and postoperative pain were excellent. Conclusion: MIVAT is a safe, reproducible technique with an indication in a minority of patients candidates to thyroidectomy and is characterized by a better postoperative discomfort.